Molecular characterization of Aedes albopictus based on the Mitochondrial cytochrome oxidase 1 marker in dengue infested areas / Nurul Ain Ismail - Ismail, Nurul Ain (2017)
The global spread of Ae. albopictus from its native range in Southeast Asia has been implicated in the recent emergence of dengue endemicity in Malaysia. Maternally inherited endosymbiont bacteria Wolbachia A (wAlbA) and B (wAlbB) strains are known to naturally infect Ae. albopictus resulting in cytoplasmic incompatibility (CI) that could reduce mosquito populations. Studies focusing on genetic diversity of Ae. albopictus and Wolbachia infestation in local populations are currently lacking in the Malaysian setting, yet such studies are crucial to enhance current vector control programs. This study was conducted to determine the pattern of Wolbachia infection in the local population using the surface protein (wsp) gene and to establish the genetic variability of maternally inherited mitochondrial DNA encoding cytochrome oxidase subunit 1 (CO1) gene in Ae. albopictus. Analysis from 12 localities in the Subang Jaya District based on temporal indices patterns were performed using 120 individual samples and 20 pooled samples for CO1 and wsp genes, respectively. Genetic polymorphism and phylogenetic analysis were conducted to reveal the genetic variability and geographic origin of Ae. albopictus and Wolbachia populations. Haplotype network was mapped to determine the genealogical relationship of sequences among groups of population in the Asian region. Genotypic detection of all sampled localities were positive for both strains with no genetic polymorphism of the wsp gene, indicating the successful introduction of Wolbachia in the Ae. albopictus populations in Subang Jaya. Comparison of local CO1 sequences with sequences derived from 5 Asian countries revealed genetically distinct intrapopulation of Ae.albopictus. Phylogenetic analysis of Ae. albopictus revealed that all local sequences descended from the same genetic lineage with the sequences from other Asian countries. Our study highlights the discovery of 20 novel haplotypes within the local population that has not been reported to date. High frequency of Wolbachia infections in Subang Jaya population may lead to low genetic diversity in Ae. albopictus due to the CI effect that may influence the genetic structure of the mosquitoes. As such, the co-existence of Wolbachia superinfection in Ae. albopictus is suggested to be beneficial towards the future development of a biological vector control agent that can be used in the local settings.